(3cJGH TaGA GdCSbGe aj hVY GdSGYGJ YdiGdQNGes - (3TgGH GdOjf CMeO Hf YeQ Hf ESeGYjd Hf eMeO Hf CHi HcQs; (3CMeO Hf YeQ Hf ESeGYjd Hf eMeO Hf CHj HcQ, GHf GdUhajs
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3aEfi deG QCjJ LeGYg ef Cgd gPG GdTCf ef GdeYGUQjf hef GdeJbOejf ajeG Sda ef GdReGf s
(3BNQgG (B:s
(3hgPG eG CQOfG HjGHg Yf CfhGY GdSGYGJ heGfOYhG GdVQhQg Edi eYQaJg s
(3Gda SfI (B675(3g`s
(3ajgG LOGhd hQShe gfOSjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B71 s
Keywords: (3Gdadcs